Pengaruh Aspek Kognitif dan Afektif terhadap Prestasi Akademik Mahasiswa - Miftaviana Zahira Zavy; Achmad Efendi; Damingun, Damingun (Yayasan Literasi Sains Indonesia, 2025)
This research aims to examine the influence of cognitive and affective aspects on the academic performance of eighth-semester students in the Bachelor of Management program at the University of Muhammadiyah East Kalimantan. Academic performance is affected by various internal and external factors, and understanding these influences is critical for improving student outcomes. Cognitive aspects refer to intellectual abilities such as critical thinking, comprehension, and analytical skills, while affective aspects involve students' attitudes, motivation, and emotional regulation during the learning process. This study employs a quantitative approach with an explanatory research design. A sample of 180 students was selected using a random sampling technique. Data were collected through a questionnaire and analyzed using multiple linear regression. The results are expected to provide insights into how both cognitive and affective aspects impact academic performance. These findings will contribute to the development of educational theory and serve as a foundation for designing more effective teaching strategies, ultimately improving student academic achievement.